Grain quality and allelic variation of the Badh2 gene in thai fragrant rice landraces - Phukjira Chan-In (2020)
© 2020 by the authors. Fragrance, which plays an important role in determining the economic value of rice to growers and consumers, is known to be controlled by the Badh2 gene. This study evaluated the grain quality characteristics and allelic variation of the Badh2 gene in 22 fragrant rice landraces from Thailand. The rice seed samples from farmers' storage facilities in northern, northeastern and southern Thailand, plus two advanced breeding lines and three check varieties, were evaluated for seed morphology and grain quality, and their Badh2 genes covering intron 4 to intron 8 were re-sequenced. Almost all of the landraces were classified as large grain types, with medium to high gelatinization temperatures. The variation in the Badh2 gene by haplotype analysis correlated with grain aroma by sensory evaluation. The badh2-E7 was found in haplotype 1 with a strong aroma in KH, NDLP, and PLD, as in KDML105 and the moderately aromatic BNM-CMU, BNM4, and SKH, along with PTT1. Three haplotypes had different positions of SNP on the Badh2 gene with varying results in the sensory test. The present results suggest that some rice varieties could be potentially introduced as genetic resources for fragrant rice breeding programs or could be developed to highly palatable cultivars with geographical indications to increase the income of highland farmers.